Aplikasi Pembelajaran pada Anak Umur 6–7 Tahun Berbasis Web: Aplikasi Pembelajaran pada Anak Umur 6–7 Tahun Berbasis Web - Vebriandi, M. Yazed; Sudarsono, Edi; Nurhayani, Nurhayani; Saputri, Meyrani (Universitas Muhammadiyah Pekajangan Pekalongan, 2025)
An application refers to the use of a computer program consisting of instructions or statements arranged in such a way that the computer can process inputs into outputs. This web-based learning application is developed to support the learning process of children aged 6–7 years through interactive and enjoyable media. By utilizing web technology, the application delivers various learning materials that cover fundamental skills such as reading, writing, arithmetic, and the introduction of other basic concepts. It is designed with a child-friendly interface, supported by engaging animations and gamification features aimed at increasing children's motivation and interest in learning.